Metode Gallery Walk sebagai strategi pembelajaran untuk menumbuhkan minat belajar sejarah (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
This study originates from the problem of students’ low interest in learning history, which is partly caused by the limited use of innovative and interactive teaching methods. As an alternative solution, the Gallery Walk method was implemented to foster active and engaging learning experiences. The main objective of this study is to determine the effect of the Gallery Walk method on students’ interest in learning history. This research employed a quantitative approach with a quasi-experimental design of the non-equivalent control group type. The population consisted of all eleventh-grade students, with class XI-A.2 (38 students) serving as the experimental group and another class (32 students) as the control group, selected through purposive sampling. Data were collected using pretest and posttest questionnaires comprising 17 items, and analyzed through normality, homogeneity, and hypothesis tests using the independent sample t-test. The results indicated a significant increase in students’ learning interest after the implementation of the Gallery Walk method, with a significance value of 0.00 < 0.05, leading to the rejection of H₀ and acceptance of Ha. These findings suggest that the Gallery Walk method has a positive and significant effect on students’ learning interest by promoting an active, collaborative, and stimulating classroom environment. Therefore, the Gallery Walk method is recommended as an effective pedagogical approach to enhance students’ engagement and appreciation of historical learning materials.
Keywords: Gallery Walk method; history learning; learning interest; innovative pedagogy quasiexperimental.